The Welfare of Animals - Clive Phillips ; edited by Clive Phillips (Springer, 2017)
The Welfare of Animals is an exciting book that will stimulate and provoke itsreaders. It describes many problems faced by animals – those we use for food,for pleasure or in research, and those simply but harshly affected by shrinkinghabitats in the face of the ever-growing human population. And yet it is not adepressing read. It focuses not only on the difficulties that animals face, but on their capacity for free-choice, for joy and excitement, and on the possible ways in which the planet can be shared between species if only we take the time andtrouble to think more carefully about the impact of our actions.